Implementasi Program Santri Husada Dalam Upaya Kemandirian Pesantren Bidang Kesehatan di Pondok Pesantren Riyadlotut Thalabah Sedan Rembang - Mardliyah, Ikhda Khullatil; Rusli, Moch; Purwanti, Sri (LENTERNAL: Learning and Teaching Journal, 2023)
Health problems in Islamic boarding schools are very diverse, such as infectious diseases, non-communicable diseases, and emergencies that can occur at any time. Regarding infectious diseases, some Islamic boarding schools fall into the risky category because they are communal and densely populated places to live. Therefore, it is necessary to have promotive and preventive efforts to prevent the spread and transmission. Pesantren efforts that are carried out to promote health in Islamic boarding schools include the development of Islamic boarding schools in the health sector to the formation of Poskestren (Pesantren Health Posts), because health is a problem that should not be underestimated but must really be a point that should be considered regularly. Riyadlotut Thalabah Islamic Boarding School is one of the Islamic boarding schools in Central Java which has had a poskestren since 2018 and has activated health education and formed a "Kader Santri Husada" as an effort to empower santri to overcome problems such as the lack of direct education. This study aims to determine the Implementation of the Santri Husada Program in Health Independence Efficiency in the Riyadlotut Thalabah Sedan Rembang. The method used in this study is a qualitative research method. The data collection process was carried out by observation and interviews with informants whose background was from pesantren caregivers, poskestren supervisors, kader santri husada and other Islamic boarding schools that adopted the program and policy makers in the health sector. From this research, it is known that Islamic boarding schools that have health education programs will make pesantren better in the health sector, as evidenced by the increasing number of students' health, health promotion efforts are accepted by the wider community through many media, duplication of the same activities in various Islamic boarding schools to get district level awards, residency, and province. This makes a positive impact on the pesantren by increasing the number of buildings managed by the poskestren, increasing the number of students each year, and becoming a brand as a healthy pesantren.